IMPLEMENTATION OF COMPUTER APPLICATION SOFTWARE FOR SOIL pH IN THE DETERMINATION OF SOIL NUTRIENT STATUS - Adekayode, Francis Omotayo (European Scientific Journal, ESJ, 2014)
The nutrient status of soils based on the soil pH was determined using the C Sharp (C#) computer program to develop an application software that revealed the relationship between the soil pH and the available essential elements in the soil. The databases were created using Microsoft Access as backend and Microsoft Visual Studio as the frontend. The database table listing parameters of Upper and Lower pH limits, Category of soil pH, Nitrogen, Phosphorus, Potassium, Calcium, Magnesium, Sulfur, Iron, Manganese, Zinc, Boron, Molybdenum, Copper and Cobalt was created in Microsoft Access and saved with .accdb file format. The Design and User Interfaces were created in Microsoft Visual Studio. When the pH was input in the space provided in the User Interface and the Load Information button clicked, the pH category and availability status of each of the essential elements were generated and displayed. The four options for the nutrient availability status were abundant, moderate, slightly and sparingly. Click once method of application publishing was used for program publishing and installation of the software on another computer.